Understanding repugnance: Implications for public policy - Julio Elias; Nicola Lacetera; Mario Macis (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2017)
Understanding the influence of moral repugnance on social decisions is challenging, particularly because in several cases not all of the relevant policy options can be observed. In a series of recent studies, we designed survey experiments to identify individual preferences in morally controversial transactions, with focus on the provision of payments to kidney donors in the United States (Elias, Lacetera and Macis 2015a-b, 2016a). We found that providing information on how a price mechanism can help alleviate the organ shortage significantly reduces opposition toward payments for organs. Moreover, we quantified the trade-off that people make between the repugnance and the efficiency of alternative kidney procurement systems. In Elias, Lacetera, Macis and Salardi (2017), finally, we analyzed how the regulation of controversial activities is related to economic development. This paper summarizes these findings and analyzes their main implications for public policy and market design.
Keywords: 330; Ethik; Organtransplantation; Marktmechanismus; Informationsverbreitung; Meinung; USA